Determination of the Composition of Fly Ash, Bottom Ash and Lime or Cement Mixtures as Road Base Material. Case Study: Road Preservation of Sp. Kereng - Bereng Bengkel – Pilang – Pulang Pisau, Central Kalimantan - Mochammad Yusuf Hilman; Noor Endah Mochtar; Soendiarto Soendiarto (Journal of Infrastructure & Facility Asset Management, 2024)
Aggregate material for road subbase layers that meet specifications is hard to find in Kalimantan Island. One alternative material is a mixture of fly ash and bottom ash (FABA) with the addition of other substances such as lime or cement as binders. It is essential to determine the optimum percentage of the fly ash, bottom ash, and lime or cement mixture to meet the requirements as road subbase material. This study was conducted by creating compositions of FABA with variations 100:0; 75:25; 50:50; 25:75; and 0:100; they were tested to determine the optimum mixture of FABA as a road subbase. Afterwards, additional materials that were cement (3%, 5%, and 7%) or lime (2%, 4%, and 6%) were added to the optimum mixture of FABA; and then, they were tested to obtain the subbase material that meets the requirement of Bina Marga specification criteria. The results show that the optimum FABA material mixture is 50:50 which has the soaked CBR value of 17.03%. Additional 7% of cement or 6% of lime give the highest values of soaked CBR and UCS. For cement, the soaked CBR value is 75.68% and the UCS value is 21.448 kg/cm2; for lime, the soaked CBR value is 60.16% and the UCS value is 27.70 kg/cm2. Based on Bina Marga specifications, SKh 1.15.1, it is known that the FABA mixture 50:50 ratio and the additional of 7% cement or 4% lime can be uses as road base materials.